A Brief Communication on Circulating PD-1-positive T-Regulatory Lymphocytes in Melanoma Patients Undergoing Adjuvant Immunotherapy With Nivolumab. Issue 7 (September 2019) - Gambichler, Thilo; Schröter, Ulrike; Höxtermann, Stefan; Susok, Laura; Stockfleth, Eggert; Becker, Jürgen C.
Abstract : Upregulation of T-regulatory lymphocytes (Tregs) is one of numerous immune escape mechanisms of malignancies. In the present pilot study we aimed to study the effect of adjuvant nivolumab during the initiation of treatment on circulating Tregs subpopulations in patients with stage III melanoma. We subsequently recruited patients with stage III melanoma who had the indication for adjuvant anti-programmed death 1 (PD-1) treatment with nivolumab. Blood collections were performed before the initiation of nivolumab and before every 2-week therapy cycle. Flow cytometry was performed for the determination of circulating CD4 + CD25highCD127 − PD-1 + (PD-1 + Tregs) and CD4 + CD25highCD127 − CTLA-4 + (CTLA-4 + Tregs) Treg populations. Circulating PD-1 + Tregs [18.1% (range, 2.9%–41.7%) vs. 4.2% (0.4%–9.8%), P =0.0001] significantly decreased after the first cycle of immunotherapy and maintained decreased during a 3-month course of treatment. By contrast, CTLA-4 + Tregs significantly increased after the first nivolumab dose when compared with CTLA-4 + Tregs before the second treatment [0.75 (0–45.5) vs. 2.1 (0.1–90.8), P =0.0002]. Blood levels of PD-1 + Tregs and CTLA-4 + Tregs remained more or less decreased and increased during a 3-month therapy with nivolumab, respectively. Data of PD-1 + Tregs as well as CTLA-4 + Tregs was not significantly associated with frequencies of immune-related adverse events ( P <0.05). In conclusion, we have demonstrated that circulating PD-1 + Tregs of melanoma patients in stage III rapidly and continuously decline after the initiation of adjuvant treatment with the PD-1 blocking antibody nivolumab. By contrast, this decline is paralleled with an increase of CTLA-4 + Tregs. The expression of PD-1 and CTLA-4 on Tregs might be a potential biomarker for the efficacy of immune checkpoint blockade in melanoma.